Effect of particle morphology on particle pick-up velocity in dry powder inhaler - Chin, Charlotte Shi Shu. (2009)
Particle entrainment is investigated by measuring the velocity required to pick up particles from rest. It is known as the pickup velocity and it is a function of the individual particle characteristics and inter-particle forces [1]. The pickup velocity of the spherical glass beads for sizes 34μm, 70μm, 170μm and 440μm is investigated using both the observational and weight loss method in the report. The work presents here focuses on the comparison of the values of pickup velocity from the calculations of various empirical correlations and the experiments. It was found out that only one of the correlations derived by Kalman et al. works for the weight loss method used in the system but not for the observational method. As for the rest of the correlations, the values do not agree with each other generally. Hence, the derived equations from various studies may not work for all particles. The comparison of values obtained from both methods will also be made and discussed. The justification for choosing the weight loss method over the observational method is also presented in the report.